Projekt edukacyjny jako strategia budowania modelu muzeum konstruktywistycznego - Kosz-Szumska, Justyna (Kultura-Społeczeństwo-Edukacja, 2024)
The paper addresses issues related to the constructivist trend and the museum educational model based on it. The first part outlines the theoretical perspective adopted, which is determined by Bruner’s constructivist approach to the learning process, providing inspiration for the museum educational model proposed by Hein. The educational project method is presented as one that can be a strategy in the implementation of such a model. The second part of this paper introduces the methodological assumptions, selected research results and conclusions. The research aimed at (a) describing the experience of students planning and implementing educational projects in the museum space, and (b) verifying whether the base and content of museum exhibitions meet the material space needs of a constructivist museum. The use of action research strategy (direct observation and document analysis) allowed to collect qualitative material, the analysis of which indicates that the implementation of educational projects, in the trend of constructivist museum model, is consistent with the assumptions of this method: among others, independence, creativity, creative and research attitude, innovation, commitment, teamwork. Finally, the author draws conclusions and recommendations for educational practice, pointing to the importance of exhibitions and the material base of museum for the implementation of museum education in the constructivist model – the need to create a learning environment in which material conditions will be understood as “tools” to help construct knowledge and meanings.